Comprehensive Review of Healthcare Workforce Development: Bridging Education, Technology, and Practice - Al-Mahmadhi, Abdullah Salem Hadi; Al-Zabadani, Raed Ali Hamad; Al Shareya, Dhafer Ali Awij; Al Shariah, Khorasan Ali Owaij; Al Shariah, Salem Ali Awij; Al- Shariah, Hassan Ali Awij; Al-Yami, Ali Saleh Awij; AL-Yami, Hamad Saeed Hamad; Al Mardif, Hassan Hamad Mani; Al Murdif, Saleh Nasser Hamad (Journal of Ecohumanism, 2024)
Healthcare is an industry in need of a highly skilled workforce owing to advancements in technology, a growing population, especially ageing, and the growing complexity of patients. This paper presents a commentary on the potential of strategies for the healthcare workforce through education, technology, and practice. These works describe the following: With reference to current literature, methods, and findings, the following challenges and opportunities emerge. The review indicates that there is a need for the use of new curricula, technology, and collaboration in order to close the gap between what is taught within classrooms and in practice. The discussion provides policy implications and describes the likely directions for forward and orderly manpower development.